THE DETERMINATION OF THE ELECTRON DENSITY BY THE S II LINES - MENDEZ, ME (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
The determination of electron density in low density objects, through the intensity ratio of forbidden lines relies heavily upon the [O II] 3727/29 ratio method. We propose an expression to derive the electron density when forbidden lines of [S II] are av
BOL OBS TONAN TACUB
Keywords: DETERMINATION, ELECTRON DENSITY, LINES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS